2014
DOI: 10.1245/s10434-013-3460-1
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM1 Long Cytoplasmic Domain Isoform is Associated with Invasion and Recurrence of Hepatocellular Carcinoma

Abstract: Background The two isoforms of carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1), 1 with a long cytoplasmic domain (CEACAM1-L) and 1 with a short (CEACAM1-S), are involved in different signaling pathways. β2-spectrin (β2SP) is an adaptor protein that plays critical roles in the proper control of Smad access to activate receptors involved in regulation of TGF-β signaling. In this study, we examined the association between CEACAM1 isoform balance and hepatocellular carcinoma (HCC) malignant pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…However, research on the genome scale indicated that the different CEACAM1 isoforms had divergent roles during tumorigenesis. CEACAM1-L (CEACAM1 long cytoplasmic domain isoform) is a risk factor for HCC recurrence and its overexpression is involved in tumor cell invasion and metastasis (30). More specifically, in this study, we demonstrated that exon 7 of CEACAM1 was the critical hub of the functional differences between the CEACAM1 isoforms.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…However, research on the genome scale indicated that the different CEACAM1 isoforms had divergent roles during tumorigenesis. CEACAM1-L (CEACAM1 long cytoplasmic domain isoform) is a risk factor for HCC recurrence and its overexpression is involved in tumor cell invasion and metastasis (30). More specifically, in this study, we demonstrated that exon 7 of CEACAM1 was the critical hub of the functional differences between the CEACAM1 isoforms.…”
Section: Discussionmentioning
confidence: 50%
“…Patients with increased inclusion levels of CEACAM1 exon 7 in HCC samples had significantly shorter survival times. Exon 7 is located on the 3'terminal of the CEACAM1 transcript, although it does not encode the immunoglobulin-like domain, the inclusion or exclusion of which may influence the subcellular location of the protein, which could remodel the tumorigenicity of CEACAM1 isoforms (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, the elevated CEACAM1 levels observed in patients with CHC might be associated with impaired cytotoxicity of NK cells. A previous report used immunohistochemical analysis to reveal that liver CEACAM1 expression correlated with the progression of HCC . We examined serum CEACAM1 levels in patients with HCC (Supporting Tables and ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous report used immunohistochemical analysis to reveal that liver CEACAM1 expression correlated with the progression of HCC. (15) We examined serum CEACAM1 levels in patients with HCC (Supporting Tables S1 and S2). The median serum level (100.8 ng/mL) in HCC patients was significantly higher than that in CHC patients (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation